Markers of Trust in the Supply Chain: From Forest Stands in Russia to End Consumers in Europe and the USA - Мария Сергеевна Тысячнюк (Journal of Economic Sociology, 2010)
This paper examines the role of different units in the supply chain to ensure consumers’ confidence in the process of production. Analysis of interviews with managers demonstrated that as we move along the supply chain upstream from the buyer to the producer, construction of trust by managers is becoming increasingly instrumental. Differences observed in the constructs of trust in various units of the supply chain can be explained by two reasons: first, by the challenges faced by each individual unit, and second by differences in value systems of managers. Thus, such intangible values as environmental friendliness and social responsibility that are the most important for the ultimate consumers do not show up in the narratives of the production managers, being replaced by a purely instrumental approach in which the trust is equivalent to the national standards and requirements of the process of production.